Factores sociodemograficos y riesgo para adherencia terapéutica en pacientes adultos con tratamiento hemodialitico Trujillo - Díaz Castillo, Nancy (2015)
This quantitative research prospective, transversal, correlational and observational court could establish the relationship between variables, sociodemographic and risk factors for adherence in adult hemodialysis patients at a clinic in Trujillo between October 2013 - January 2014; supported by the theoretical bases of Sabate (2004) on the five dimensions for interacting adherence to longterm therapies: evidence for action, WHO, and the factors that influence adherence Brannon (2002); the sample universe consisted of 67 randomly selected patients that met the inclusion criteria; the instrument was used to assess factors influencing adherence in hemodialysis patients, developed by the author. In the data processing became a pattern of automated tabulation with the help of the SPSS-18.0 and the marginal homogeneity test of Chi square was applied, the test was significant if the p-value <0.05. The results showed that only the relationship between level of education and degrees of risk for adherence showed a significant difference, no clear and consistent relationship between the degree of adherence and other socio-demographic variables were found. It is concluded that 50% of the population is evaluated low symbolizing a good prognosis for adherence in adult investigated risk.